2010
DOI: 10.1007/s11104-010-0375-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization and fire act independently on foliar stoichiometry in a temperate steppe

Abstract: Nitrogen (N) fertilization, as a grassland management strategy, has been widely used to improve forage quality and increase the productivity of grasslands degraded by overstocking. It is widely accepted that N addition will alter ecosystem structure and function, and that these effects may be altered by natural disturbances, such as fire. We examined the effects of annual burning and N fertilization (17.5 g N m −2 year −1 , at a surplus rate in order to simulate agriculture treatment) on foliar chemistry and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 51 publications
(80 reference statements)
7
18
1
Order By: Relevance
“…The higher leaf N content and N: P may reflect the high N availability in the N treatments . In this study, the N: P ratios were significantly higher in the N treatments, due to the greater availability of N than P, consistent with previous studies (Craine et al, 2008;Cui et al, 2010). The N treatments had higher C: P ratios than the non-N treatment, but no significant differences were found between N treatments at anthesis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The higher leaf N content and N: P may reflect the high N availability in the N treatments . In this study, the N: P ratios were significantly higher in the N treatments, due to the greater availability of N than P, consistent with previous studies (Craine et al, 2008;Cui et al, 2010). The N treatments had higher C: P ratios than the non-N treatment, but no significant differences were found between N treatments at anthesis.…”
Section: Discussionsupporting
confidence: 92%
“…The C: P ratio had a similar trend to the N: P. Maximum N: P was in the flag leaf, which caused by the lower P content. The higher C: P ratios in the N treatments were probably caused by the decrease in P as N fertilizer application and consistent with the results reported by Cui et al (2010) for N addition in a temperate steppe ecosystem. N and P content decreased from anthesis to harvest stages, leading C: N and C: P ratios increase in harvest.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No significant difference was found between this study and previous report (Wang et al, 2014) and between lucerne and other species from larger scales (Elser et al, 2000;He et al, 2008;McGroddy et al, 2004;Reich and Oleksyn, 2004;Townsend et al, 2007;Zheng and Shangguan, 2007). This result differs a lot from what we knew from a semi-arid grassland of China (Cui et al, 2010), in which the legume shrub showed the highest foliar N:P. However, in most cases lucerne leaf N:P was higher than the global values, possibly resulting from the very high Volume 39 Issue 4 (2016) 599 N concentration of leguminous lucerne with strong BNF. Dramatically, leaf N:P of other legumes (He et al, 2008) and tropical rainforests (Townsend et al, 2007) were higher than those of lucerne leaf.…”
Section: Resultscontrasting
confidence: 95%
“…These values were much lower than those of other species from larger scales (Elser et al, 2000;He et al, 2006;McGroddy et al, 2004;Zheng and Shangguan, 2007). Generally leguminous species has the lowest C:N than other species (Cui et al, 2010) due to more N accumulation. There was significant cut effect on leaf C:N of lucerne, in agreement with Wang et al (2013).…”
Section: Resultsmentioning
confidence: 71%